Agricultural dust explosions in 2012 - Ambrose, R. P. Kingsly (Kansas State University. Dept. of Grain Science and Industry, 2015)
There were 10 dust explosions reported in the U.S. in 2012 according to Kingsly Ambrose, Assistant Professor, Kansas State University. This compares to 9 in 2011 and a ten-year average of 10.0 explosions.
Keywords: Grain dust; Dust explosions